The Affective Life of the Average Man : The Victorian Novel and the Stock-Market Graph - Fakhri, Ahmed, 1949- (Book collections on Project MUSE., 2014)
By examining Arabic legal opinions, Ahmed Fakhri seeks to understand how the organization of these texts accomplishes specific social goals. In doing so, he hopes to illuminate socio-cultural practices among those who produce and use these texts. Like other sociolinguistics projects, this manuscript unites texts with their social contexts. Fakhri also points out that legal texts have traditionally held an important place in Arabic culture and therefore provide an especially illuminating window into the broader realm of Arabic thought and culture.